A CAUSAL MACROECONOMIC MODEL OF DEVALUATION AND INFLATION IMPACT ON THE ECONOMY OF UKRAINE - Vasylenko, Yuriy; Bazhenova, Olena (Ekonomika, 2014)
Abstract. The macroeconomic model of Ukraine, based on a complete system of real microeconomic mechanisms (formation of prices, costs, salary, manufacturers’ and state incomes, taxes, etc., trade and transfers among all agents) has been developed. The groups of goods, producers and consumers behaving equally in the conditions of devaluation and inflation have been formed. The core of modeling the interrelation between price, cost price and income is dividing all goods into those of final and intermediate consumption. The traditional macroeconomic hypotheses (equilibrium, SNA balances, influence of money supply, etc.) turned out to be particular cases. The model can be modified for any country. It was has been found that both devaluation and inflation always reduce the real GDP. Conditions of the growth of the value added of exports have been defined. A relationship among emission, devaluation, and inflation has been derived.Key words: macroeconomic model, microeconomic mechanisms’ system, intermediate consumption, non-equilibrium, new goods’ aggregation, devaluation, inflation